Intimate intertwining of the pathogenesis of hypoxia and systemic sclerosis: A transcriptome integration analysis - He, Xinglan; Shi, Yaqian; Zeng, Zhuotong; Tang, Bingsi; Xiao, Xuan; Yu, Jiangfan; Zou, Puyu; Liu, Jiani; Xiao, Yangfan; Luo, Yangyang; Xiao, Rong (Frontiers in Immunology, 2022)
(1) Objectives: Systemic sclerosis (SSc) is an autoimmune disease caused by various pathogenic factors, including hypoxia. Hypoxia stimulates the production of the extracellular matrix to promote fibrosis. However, the integrated function and underlying mechanism of hypoxia in SSc is unclear. (2) Methods: In the present study, we used Agilent SurePrint G3 Human Gene Expression v3 for the transcriptional sequencing of fibroblasts with and without hypoxia to detect differentially expressed genes (DEGs) in hypoxia. We analyzed the results with the transcriptome data of SSc lesions (GSE95065) to select the co-DEGs. Then, GO and KEGG enrichment analyses were performed based on the co-DEGs using the R package ClusterProfiler, which showed that hypoxia and crosstalk of hypoxia with other pathogenic factors are involved in the pathogenesis of SSc. Furthermore, we constructed a PPI network of co-DEGs and screened two significant functional expression modules. (3) Results： We identified nine hub genes (ALDH1A1, EGF, NOX4, LYN, DNTT, PTGS2, TKT, ACAA2, and ALDH3A1). These genes affect the pentose phosphate pathway, oxidative stress, and lipolysis. (4) Conclusion: Our study provides insights into the mechanisms underlying the effects of hypoxia on SSc pathogenesis, which will help to better understand SSc pathogenesis and develop new therapeutic strategies for SSc.